KNOWLEDGE AND SKILLS OF PROFESSIONAL COMMUNICATION AS THE EMPLOYABILITY SUPPORT FACTOR - Matulcikova, Marta; Brevenikova, Daniela (European Scientific Journal, ESJ, 2015)
Economic and social changes as well as changes in technologies can transform the character of professional life and building one’s career. Across regions of the Slovak Republic, these processes lead to differences between the level of completed qualifications of human resources and the creation of job opportunities. The focus is on an active foreign language proficiency, which is viewed as a key factor supporting employability. The ability to successfully communicate on-the-job or when applying for it is discussed on the basis of long-term experience in learning and teaching English for Specific Purposes as well as research in language education and intercultural communication. Results of a survey on the importance of studying languages for professional purposes carried out in four student groups at a noneconomic faculty in Bratislava, Slovakia are analysed and evaluated in two chapters. The presentation is a partial result of the second stage of the research carried out under the research project KEGA 006EU-4/2013 – “Methods and principles applied in the preparation of structure and content of the subject disciplines supporting the development of economics knowledge and business skills in students of non-economic study programmes of the second cycle of higher education”.